1987
DOI: 10.1507/endocrj1954.34.189
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides Turnover and Insulin Secretion in Pancreatic Islets

Abstract: The relationship between glucose-induced insulin secretion and metabolism of inositol phospholipid was investigated by means of an islet perifusion method and direct measuring of inositol phosphates after sonicating the islets. The results showed that the time course of inositol phospholipid breakdown is coincident with the first phase of glucose-induced insulin secretion. Analysis of the effluent perifusate as well as the water soluble inositol-containing substance after sonication of stimulated islets reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Thus, the absolute and relative (% of maximal) accelerations of 86Rb+ efflux by 0.1,IM-ACh were more than twice as large in the absence as in the presence of Ca2l. inositol and then perifused under conditions similar to ours is an index of phosphatidylinositol breakdown [26][27][28][29]. Our results show that the acceleration of 3H efflux by ACh was dose-dependent, and confirm that it is only partially inhibited by omission of extracellular Ca2+ [28].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, the absolute and relative (% of maximal) accelerations of 86Rb+ efflux by 0.1,IM-ACh were more than twice as large in the absence as in the presence of Ca2l. inositol and then perifused under conditions similar to ours is an index of phosphatidylinositol breakdown [26][27][28][29]. Our results show that the acceleration of 3H efflux by ACh was dose-dependent, and confirm that it is only partially inhibited by omission of extracellular Ca2+ [28].…”
Section: Discussionsupporting
confidence: 79%
“…3H efflux from islets preloaded with myo- [2-3H]inositol was measured in the same system by using batches of 50 islets for each experiment, after 2 h of loading with the tracer. Previous studies [26][27][28][29] have shown that the 3H-labelled products released from islets preloaded with myo-[2-3H]inositol consist of free inositol (> 70 %) and inositol phosphates. Those four studies concluded that the acceleration of 3H efflux brought about by several secretagogues, including muscarinic agonists [28], reflects phosphoinositide breakdown.…”
Section: Egtamentioning
confidence: 99%